Workshop on Preparation of Teaching Tools for Local Content of Manggarai Culture with a Culturally Responsive Teaching Model for Elementary School Teachers throughout Manggarai Regency - Marianus Tapung (Jurnal Indonesia Sosial Teknologi, 2024)
The Workshop on the Preparation of Teaching Tools for Local Content of Manggarai Culture with the Culturally Responsive Teaching (CRT) Model for Elementary School Teachers throughout Manggarai Regency aims to improve teachers' understanding and skills in integrating local culture into learning in schools. This workshop was held in response to the need for a more relevant and inclusive learning approach for students in Manggarai District. Through a series of training sessions, working group discussions, and presentations, participants were given knowledge and practical skills in developing teaching tools that are responsive to Manggarai culture, utilizing CRT principles. Teachers have been in the process of identifying, mapping, and integrating elements of local culture into lesson planning documents and learning tools, thus opening up space for more meaningful and relevant learning experiences for elementary school students in Manggarai. The workshops also provide a space and platform for the exchange of ideas and experiences between teachers, strengthen pedagogic insights, establish communication and collaboration, foster collective awareness, build their professional networks, and build sustainable learning communities. With the involvement of teachers in this workshop, it is expected to contribute to improving the quality of education in Manggarai District, while strengthening and promoting the rich and valuable local cultural heritage.